2011
DOI: 10.1093/humrep/der120
|View full text |Cite
|
Sign up to set email alerts
|

Do women with ovaries of polycystic morphology without any other features of PCOS benefit from short-term metformin co-treatment during IVF? A double-blind, placebo-controlled, randomized trial

Abstract: There appears to be no benefit in metformin co-treatment before and during IVF in women with PCO without any other features of PCOS. Clinical Trials.gov: NCT01046032.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
3
12
0
1
Order By: Relevance
“…Our study also showed significantly higher serum E2 concentrations and more follicles in the PCO morphology group compared to controls. These findings are again consistent to what has been demonstrated in the literature in both PCOS and PCO morphology patients [12,20,24]. We also observed that women with PCO morphology had on average 2 more oocytes retrieved than controls, but this difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study also showed significantly higher serum E2 concentrations and more follicles in the PCO morphology group compared to controls. These findings are again consistent to what has been demonstrated in the literature in both PCOS and PCO morphology patients [12,20,24]. We also observed that women with PCO morphology had on average 2 more oocytes retrieved than controls, but this difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…However, some elements of the response to ovarian stimulation in our study are different from what has been shown in the past for patients with PCOS or PCO morphology. Increased sensitivity to gonadotropins has been demonstrated in the literature in patients with PCOS [20] and also with PCO morphology in an older study [24], likely due to a larger cohort of FSH sensitive follicles [23]. Our study also agrees with the above literature showing that donors with PCO morphology are more responsive to gonadotropins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, studies have shown that for PCOS patients undergoing IVF treatment, short-term cotreatment with metformin neither enhances the response to the stimulation nor improves the fertilization rate, but does improve the pregnancy outcome [82]. In addition, more recent studies and reviews have shown that cotreatment with metformin before or during IVF cycles does not improve live birth rates, pregnancy rates or severe OHSS [79,83] …”
Section: Endocrinological Insights Into Different In Vitro Fertilizatmentioning
confidence: 99%